Comparison of Social Validity Ratings With the Effects of a Video-Feedback Intervention for Communication Partners of Individuals With Deafblindness - Damen, Saskia; Schuengel, Carlo; Ruijssenaars, Wied; Janssen, Marleen J. (Frontiers in Education, 2021)
The parents, teachers, and professional caregivers of individuals with disabilities may benefit from interventions to enhance their educational skills. In previous studies, positive effects were observed of a video-feedback intervention for caregivers (i.e. parents, teachers, and professional caregivers) on their communication with an individual with congenital deafblindness. The intervention they received, was the High-Quality Communication (HQC) intervention. The aim of the current study was to gain insight into the perceived relevance, feasibility, and effectiveness (i.e., social validity) of the HQC-intervention according to these caregivers, and the correspondence between the social validity ratings and the observational effects of the HQC-intervention. Responses on the Social Validity Scale from 25 caregivers who participated in the High-Quality Communication (HQC) intervention revealed that they considered the HQC intervention to be a relevant, feasible, and effective intervention. Comparing the caregiver ratings with observational effects of the HQC intervention at the individual case level, we found no association between the observed effectiveness of this intervention and caregivers’ opinions about its relevance, feasibility and effectiveness. There was however, an association between the rated feasibility and effectiveness, which suggests that the perceived success of the intervention was influenced by caregivers’ experienced competency in supporting the communication of individuals with CDB. The combination of observational and social validity data enabled a critical analysis of the clinical value of the HQC intervention. We recommend that future studies use multiple data source for social validity assessment.